Corregidor in peace and war - Hubbard, Charles M. 1939- (University of Missouri Press, 2006)
"Around 1898, the American military began to arm and fortify 'the Rock,' an island located at the entrance of Manila Bay. Heavily illustrated with historic and current photographs, Corregidor in Peace and War documents island life before WWII, and then records its loss and recapture during the struggle with Japan"--Provided by publisher.